2018
DOI: 10.1111/jicd.12385
|View full text |Cite
|
Sign up to set email alerts
|

Topical hyaluronic acid in the management of oral lichen planus: A comparative study

Abstract: Lichen planus is a chronic mucocutaneous inflammatory disorder that is estimated to affect 0.5%-2.2% of the general population. 1 The cause is unknown in most cases; however, in a minority of patients, precipitating factors have been suggested, including dental materials, drugs, stress, and infectious agents. 2 It primarily affects middleaged adults, and the prevalence is greater among women. There are four forms of oral lichen planus (OLP) that relate to clinical appearance: reticular, atrophic, bullous, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
(17 reference statements)
1
24
0
2
Order By: Relevance
“…In a study evaluating the efficacy of a 0.2% topical hyaluronic acid gel preparation in the management of OLP patients, the test group showed only transient improvements for up to 4 hours post-application. There were no differences between treatment groups at any of the time intervals, and HA, as well as placebo, had no effect on the extent and severity [25]. These data corroborate our findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a study evaluating the efficacy of a 0.2% topical hyaluronic acid gel preparation in the management of OLP patients, the test group showed only transient improvements for up to 4 hours post-application. There were no differences between treatment groups at any of the time intervals, and HA, as well as placebo, had no effect on the extent and severity [25]. These data corroborate our findings.…”
Section: Discussionsupporting
confidence: 90%
“…While some authors related the positive immediate effect on pain in OLP [25] or patients with oral ulcers to a barrier effect of HA [61], Romeo et al found no difference in pain perception in biopsy wounds treated with a gel containing amino acids and 1.33% HA versus no gel, despite faster healing [62]. Interestingly, proteins essential for lubrication and viscoelasticity were missing in saliva from OLP patients [63], possibly rendering them more sensitive to the beneficial effects of HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐thousand seven‐hundred and fifteen articles were retrieved with the search strategy and two from the cross‐references. Out of 2717, 55 studies 13–67 were included in the systematic review encompassing 2831 patients. Three studies did not report their outcomes amenable for calculating the pooled estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Hyaluronic acid is an effective substitute for topical corticosteroid with similar results. Moreover, in severely painful OLP, 0.2% HA could be used in addition to other topical drugs, such as corticosteroids and calcineurin inhibitors, to reduce the overall amount of immunosuppressant therapy used in a course of treatment [30].…”
Section: Discussionmentioning
confidence: 99%